Into that forest - Nowra, Louis, 1950- (London : EGMONT, 2013)
We were lost, and the only thing that could help us were the tiger. The more I looked at its black eyes, the more I seen kindness, and I knew it were saying to us, Come, I'll take you home. This is the story of two girls lost in the Tasmanian bush, saved and raised by two Tasmanian tigers.
Keywords: Tasmania -- Juvenile fiction; Tiger -- Juvenile fiction; Human-animal relationships -- Juvenile fiction